A influência da semente de linhaça como fonte de fitoestrógenos nos indicadores cardiovasculares e na menopausa de ratas castradas - Pacheco, Juliana Tomaz (2006)
Flaxseed has attracted the interest of the scientific community for presenting innumerable benefits to the health. It was objectified to randomly evaluate the influence of this seed in the cardiovascular pointers and the menopause of 21 Wistar rats that had been submitted to bilateral oophorectomy for induction of surgical menopause, drafted in three groups: Control Group (GC) fed with ration of casein; Flaxseed Group (GL) fed with ration of casein, added of 25% of flaxseed and Modified Control Group (GCM) fed with ration of casein, added of staple fibers and fat. All the rations with 10% of protein were elaborated according to recommendations of AIN 93. The rats were kept in environment with temperature (22ºC ± 2ºC) and adequate illumination (clearly/dark cycle of 12 in 12 hours), receiving ration and water. It was collected every two days the consumption of ration (g) and variation of weight (g) for determination of the alimentary profile of the animals. The vaginal cytology was collected every 30 days, fixed in microscopic slides and stained by the Papanicolaou technique. After 180 days, the rats were anesthetized with thiopental (Tiopentax® - 0.15 ml/100g bw, i.p.), for the collection of the blood by cardiac puncture. It was determined the serum total cholesterol concentrations and fractions (HDL-c, LDL-c and VLDL-c) and triglycerides through LABTEST® s biochemist. Furthermore, the determination of 17β-estradiol was carried through with Diagnostics Products Corporation s kits (DPC®) with radioimunotest. The non-parametric test of Kruskal-Wallis was used. In case of significant differences, the post hoc U test of Mann-Whitney was applied for peer groups comparison through the Sofware S-Plus version 6.0, with the level of p≤0.05. Significant total cholesterol reduction of the GL in relation to the others groups was observed (p=0.0005), as well as an (non-significant) increase of the HDL-c of the same group (p=0.0745), however, it was not observed modification for the data of LDL-c, VLDL-c and triglycerides. The ration consumption was similar between the groups, however the weight variation was different (p=0.0005). Although presenting superior value of 17β-estradiol (p=0.0012) in relation to the others groups, the GL did not demonstrate influence in the vaginal cytology of the rats. The data had demonstrated that the addition of flaxseed to the rations in such a way had a positive influence on the lipidic profile as much as on the alimentary profile of the animals and that although presenting a significant estrogenic action, this was not enough to modify the vaginal cytological profile of the animals.